Eimeria nycteae sp. n. (Apicomplexa: Eimeriidae), a new parasite species from the snowy owl, Nyctea scandiaca - Wolf, Jiří; Koudela, Břetislav; Modrý, David
Coprological examinations of three snowy owls, Nyctea scandiaca (L.) revealed the presence of a coecidium of the genus Eimeria that apparently represents a previously undescribcd species. Oocysts of Eimeria nycteae sp. n. were spherical to subspherical, 23.6 (23-25) x 22.2 (22-23) pm with a shape index 1.1 (1.0-1.1). The oocyst wall was bilayered, smooth - 0.75 pin thick. A polar granule was absent. Sporocysts were ellipsoidal, 18.5 (18-19) x 9.8 (9-10) pm with a shape index 1.9 (1.8-2.1) with Stieda and substieda bodies. A sporocyst residuum was present as small granules scattered among sporozoitcs. The sequence of the sporulation process of this new species is given and illustrated with photomicrographs. Owls examined did not exhibit any signs of alteration of their health status.